2020
DOI: 10.1016/j.heliyon.2020.e04789
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oil pulling with coconut oil to improve dental hygiene and oral health: A systematic review

Abstract: Objectives: Coconut oil is a cheap and accessible oil for many people around the world. There are numerous advocates for the practice of oil pulling to prevent common oral diseases. Therefore determining the effectiveness of oil pulling with coconut oil could potentially have monumental benefits. This review aimed to assess the effect of oil pulling with coconut oil in improving oral health and dental hygiene. Data: We included randomized controlled trials comparing the effect of oil pulling with coconut oil o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 35 publications
0
26
0
1
Order By: Relevance
“…Moreover, it does not require any specialized oil, and any household oil (such as sunflower or any other vegetable oil) can be used. The limited evidence suggests that oil pulling with coconut oil may improve oral health and dental hygiene [ 77 ]. Coconut oil has shown significant antifungal activity, comparable to that of ketoconazole and chlorhexidine [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it does not require any specialized oil, and any household oil (such as sunflower or any other vegetable oil) can be used. The limited evidence suggests that oil pulling with coconut oil may improve oral health and dental hygiene [ 77 ]. Coconut oil has shown significant antifungal activity, comparable to that of ketoconazole and chlorhexidine [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 2 ] These claims of tempting benefits drive oil pulling's popularity as widely seen in various media; however, scientific evidence that supports or contradicts such claims is still lacking. [ 3 4 ] For oral health, a few studies reported a significant reduction in plaque index, gingival index (GI), modified GI scores, and levels of Streptococcus mutans after coconut oil pulling. [ 5 6 7 8 9 10 11 ] Coconut oil and palm oil (PO) have long been used as common cooking oil and are commercially available worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an increasing trend in herbal therapeutics drives the need to identify a natural product that may be useful for preventing periodontal disease. There are many reports of using common oils, such as coconut, for rinsing the mouth [12]. This method of oil pulling is known to facilitate the removal of bacteria mechanically.…”
Section: Introductionmentioning
confidence: 99%